2007
DOI: 10.2214/ajr.06.1238
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric and MRI Study of the Musculotendinous Contributions to the Capsule of the Symphysis Pubis

Abstract: Cadaver and MRI findings show an intimate relationship between the adductor longus; rectus abdominis; and symphyseal cartilage, disk, and capsular tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 21 publications
3
59
1
6
Order By: Relevance
“…However, several studies have proposed that MRI is not necessarily a means of diagnosing athletic pubalgia but, rather, is more useful for retrospectively confirming the diagnosis, intraoperative findings, or both [3,17,18]. Other investigators have reported that imaging studies, including MRI studies, performed for the evaluation of athletic pubalgia are most often negative [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have proposed that MRI is not necessarily a means of diagnosing athletic pubalgia but, rather, is more useful for retrospectively confirming the diagnosis, intraoperative findings, or both [3,17,18]. Other investigators have reported that imaging studies, including MRI studies, performed for the evaluation of athletic pubalgia are most often negative [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…MRI 7 8 shows that the pubic symphysis' appearance is age-dependant with all participants under 21 years demonstrating a pubic apophysis. Robinson et al 7 concluded that "this junction of the pubis, apophysis and soft tissue might be expected to represent an area of biomechanical weakness that endures considerable forces during athletic single stance manoeuvres. "…”
Section: Introductionmentioning
confidence: 99%
“…It is still debatable, if the diagnosis of osteitis pubis and instability of just more than 2 mm justifies this invasive procedure, keeping the athletes for a long period of time away from sports. The stability of symphysis pubis is maintained by a stable ligamentous envelope which is formed by four different pubic ligaments, together with the adjacent tendons of the rectus and the adductors [11]. Among these ligaments, strong anterior and inferior (arcuate) pubic ligament reinforces the symphysis pubis to resist the forces applied to the joint during physiologic gait [12].…”
Section: Discussionmentioning
confidence: 99%